Gas chromatography-mass spectrometry and single nucleotide polymorphism genotype by sequencing analyses reveal the bean chemical profiles and relatedness of Coffea canephora genotypes in Nigeria - Anagbogu, C.F.; Ilori, C.O.; Bhattacharjee, Ranjana; Olaniyi, O.O.; Beckles, D.M. (MDPI, 2019)
The flavor and health benefits of coffee (Coffea spp.) are derived from the metabolites that accumulate in the mature bean. However, the chemical profiles of many C. canephora genotypes remain unknown, even as the production of these coffee types increases globally. Therefore, we used Gas Chromatography-Mass Spectrophotometry to determine the chemical composition of C. canephora genotypes in Nigeria—those conserved in germplasm repositories and those cultivated by farmers. GC-MS revealed 340 metabolites in the ripe beans, with 66 metabolites differing (p-value < 0.05) across the represented group. Univariate and multivariate approaches showed that the ‘Niaouli’ genotypes could be clearly distinguished from ‘Kouillou’ and ‘Java’ genotypes, while there was almost no distinction between ‘Kouillou’ and ‘Java,’. Varietal genotyping based on bean metabolite profiling was synchronous with that based on genome-wide Single Nucleotide Polymorphism analysis. Across genotypes, the sucrose-to-caffeine ratio was low, a characteristic indicative of low cup quality. The sucrose-to-caffeine ratio was also highly correlated, indicative of common mechanisms regulating the accumulation of these compounds. Nevertheless, this strong correlative link was broken within the ‘Niaouli’ group, as caffeine and sucrose content were highly variable among these genotypes. These ‘Niaouli’ genotypes could therefore serve as useful germplasm for starting a Nigerian C. canephora quality improvement breeding program.